THE IMPACT OF SOCIAL MEDIA ON YOUTH BEHAVIOR - Sabirbaeva Guljayna Saparbay qizi; Jumabaeva Dinara Orazbay qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the impact of social media on youth behavior in the modern digital world. With the rapid growth of internet technologies, social media platforms have become an essential part of young people’s daily lives. The study analyzes both the positive and negative influences of social media, focusing on communication, education, mental health, and lifestyle changes. While social media provides opportunities for learning, creativity, and global interaction, it also presents risks such as addiction, cyberbullying, and decreased academic performance. The article highlights the importance of balanced and responsible use of social media to ensure healthy development among youth.